Risk Factors for Acute Respiratory Tract Infection (ARI) Incidence in the Coastal Community of Liwuto Village - Wa Ode Azfari Azis; Novya Putri Ramadhani; Dahmar; Rininta Andriani (International Journal of Health, Economics, and Social Sciences (IJHESS), 2026)
Background: Cases of Acute Respiratory Infection (ARI) in the service area of Liwuto Health Center continue to rise, from 318 cases (2021) to 472 cases during the period of January–October 2024, with children under five as the most vulnerable group. Research Objective: This study aims to identify risk factors associated with the incidence of ARI among coastal communities within the service area of Liwuto Health Center. Methods: This was an analytic observational quantitative study with a cross-sectional design. The population consisted of 203 children under five, with a sample of 67 respondents calculated using the Slovin formula and selected through accidental sampling. Data analysis used univariate and bivariate (chi-square) tests. Results: Variables significantly associated with ARI incidence were exposure to cigarette smoke (p=0.000), Clean and Healthy Living Behavior (PHBS) (p=0.000), house ventilation (p=0.000), residential density (p=0.000), and type of house wall (p=0.024). Conclusion: There is an association between exposure to cigarette smoke, PHBS, house ventilation, residential density, and type of wall and the incidence of ARI. Education from the Health Center regarding environmental hygiene and clean and healthy living behaviors is needed to prevent ARI transmission in coastal communities.